Relevant domains, core outcome sets and measurements for implant dentistry clinical trials: The Implant Dentistry Core Outcome Set and Measurement (ID‐COSM) international consensus report - Tonetti, Maurizio S.; Sanz, Mariano; Avila‐Ortiz, Gustavo; Berglundh, Tord; Cairo, Francesco; Derks, Jan; Figuero, Elena; Graziani, Filippo; Guerra, Fernando; Heitz‐Mayfield, Lisa; Jung, Ronald E.; Lai, Hongchang; et al. (Journal of clinical periodontology, 2023)
Aim Lack of consistently reported outcomes limits progress in evidence‐based implant dentistry and quality of care. The objective of this initiative was to develop a core outcome set (COS) and measurements for implant dentistry clinical trials (ID‐COSM). Materials and Methods This Core Outcome Measures in Effectiveness Trials (COMET)‐registered international initiative comprised six steps over 24 months: (i) systematic reviews of outcomes reported in the last 10 years; (ii) international patient focus groups; (iii) a Delphi project with a broad range of stakeholders (care providers, clinical researchers, methodologists, patients and industry representatives); (iv) expert group discussions organizing the outcomes in domains using a theoretical framework and identifying the COSs; (v) identification of valid measurement systems to capture the different domains and (vi) final consensus and formal approval involving experts and patients. The methods were modified from the best practice approach following the Outcome Measures in Rheumatoid Arthritis Clinical Trial and COMET manuals. Results The systematic reviews and patient focus groups identified 754 (665 + 89, respectively) relevant outcome measures. After elimination of redundancies and duplicates, 111 were formally assessed in the Delphi project. By applying pre‐specified filters, the Delphi process identified 22 essential outcomes. These were reduced to 13 after aggregating alternative assessments of the same features. The expert committee organized them into four core outcome areas: (i) pathophysiology, (ii) implant/prosthesis lifespan, (iii) life impact and (iv) access to care. In each area, core outcomes were identified to capture both the benefits and harms of therapy. Mandatory outcome domains included assessment of surgical morbidity and complications, peri‐implant tissue health status, intervention‐related adverse events, complication‐free survival and overall patient satisfaction and comfort. Outcomes deemed mandatory in specific circumstances comprised function (mastication, speech, aesthetics and denture retention), quality of life, effort for treatment and maintenance and cost effectiveness. Specialized COSs were identified for bone and soft‐tissue augmentation procedures. The validity of measurement instruments ranged from international consensus (peri‐implant tissue health status) to early identification of important outcomes (patient‐reported outcomes identified by the focus groups). Conclusions The ID‐COSM initiative reached a consensus on a core set of mandatory outcomes for clinical trials in implant dentistry and/or soft tissue/bone augmentation. Adoption in future protocols and reporting on the respective domain areas by currently ongoing trials will contribute to improving evidence‐informed implant dentistry and quality of care.